2024
DOI: 10.3390/ijms25020794
|View full text |Cite
|
Sign up to set email alerts
|

Heart Failure with Preserved Ejection Fraction: The Pathophysiological Mechanisms behind the Clinical Phenotypes and the Therapeutic Approach

Laurențiu Stoicescu,
Dana Crişan,
Claudiu Morgovan
et al.

Abstract: Heart failure (HF) with preserved ejection fraction (HFpEF) is an increasingly frequent form and is estimated to be the dominant form of HF. On the other hand, HFpEF is a syndrome with systemic involvement, and it is characterized by multiple cardiac and extracardiac pathophysiological alterations. The increasing prevalence is currently reaching epidemic levels, thereby making HFpEF one of the greatest challenges facing cardiovascular medicine today. Compared to HF with reduced ejection fraction (HFrEF), the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 250 publications
0
8
0
Order By: Relevance
“…Microvascular dysfunction, oxidative stress, inflammation, and senescence have been proposed as etiological factors of HFpEF [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Microvascular dysfunction, oxidative stress, inflammation, and senescence have been proposed as etiological factors of HFpEF [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Alterations in growth signaling pathways, including insulin-like growth factor-1 (IGF-1), have also been reported in the absence of CVD, confirming the direct relationship between senescence and HFpEF [ 8 ]. Circulating molecules such as the vascular endothelial growth factor, IL-1, IL-8 cytokines, matrix metalloproteinase, and the plasminogen activator inhibitor (PAI)-1 have been recognized as being involved in the mechanisms sustaining inflammation and oxidative stress tissue remodeling [ 5 ]. This secretory pattern has been hypothesized to promote the development of HFpEF [ 5 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparatively, HFpEF patients tend to be female, elderly, and commonly have associated comorbidities such as hypertension, diabetes, obesity, chronic renal failure, and atrial fibrillation, in contrast to those with HFrEF. 2 Despite the increasing prevalence and poor prognosis associated with HFpEF, identifying patients who will experience unfavourable outcomes within this heterogeneous group remains exceedingly difficult. Beyond LVEF, a prompt and accurate diagnosis is therefore a key challenge for improving the prognosis of these patients.…”
mentioning
confidence: 99%
“…The aetiology of this pathophysiology remains unclear, multifactorial and related to systemic inflammation leading to endothelial dysfunction, microvascular dysfunction and general oxidative stress. 2 Microvascular dysfunction contributes significantly to structural and functional alterations. 13,14 Numerous studies have shown that HFpEF should not be regarded as a single entity but rather as a heterogeneous spectrum comprising various epidemiological, clinical, biomarker, and prognostic profiles within the population.…”
mentioning
confidence: 99%